Kepuasan Hidup Pekerja Perempuan: Sebuah Tinjauan Konseptual - Muthia Pramesti; Isbandi Rukminto Adi; Riani Rachmawati (JURNAL SOSIAL HUMANIORA (JSH), 2021)
This paper aims to conduct a conceptual study of factors that drive life satisfaction in the work domain for female workers. They experience several problems related to human resource policies related to their personal and work life. The dual role as breadth winner and housewife often take place. Life satisfaction is interesting to be discussed due to the well-being challenges for female workers. The framework is built by “Top-Down” and “Bottom-Up” theory. The author conducted an electronic-based data search from 58 articles during the 2019-2021 period. Several factors affect job satisfaction, such as need fulfilment, self-development and work pressure. The discussion section will explain the factors driving workers' life satisfaction to life, especially for female workers.